How Emotion Relates to Language and Cognition, Seen Through the Lens of Evaluative Priming Paradigms - Rohr, Michaela; Wentura, Dirk (Frontiers in Psychology, 2022)
Affect and emotion are essential aspects of human life. These states or feelings signal personally relevant things or situations and color our memories and thoughts. Within the area of affective or emotion processing, evaluation–the assessment of the valence associated with a stimulus or event (i.e., its positivity or negativity)–is considered a fundamental process, representing an early and crucial stage in constructivist emotion theories. Valence evaluation is assumed to occur automatically when encountering a stimulus. But does this really apply always, even if we simply see a word? And if so, what exactly is processed or activated in memory? One approach to investigating this evaluative process uses behavioral priming paradigms and, first and foremost, the evaluative priming paradigm and its variants. In the present review, we delineate the insights gained from this paradigm about the relation of affect and emotion to cognition and language. Specifically, we reviewed the empirical evidence base with regard to this issue as well as the proposed theoretical models of valence evaluation, specifically with regard to the nature of the representations activated via such paradigms. It will become clear that affect and emotion are foremost (and, perhaps, even exclusively) triggered by evaluative priming paradigms in the sense that semantic affective knowledge is activated. This knowledge should be modeled as being active in working memory rather than in long-term memory as was assumed in former models. The emerging evidence concerning the processing of more specific emotion aspects gives rise to the assumption that the activation of these semantic aspects is related to their social importance. In that sense, the fast and (conditionally) automatic activation of valence and other emotion aspects in evaluative priming paradigms reveals something about affect and emotion: Valence and specific emotion aspects are so important for our daily life that encountering almost any stimulus entails the automatic activation of the associated valence and other emotion aspects in memory, when the context requires it.